Critical Case Insights from Mali : Strengths and Opportunities for Education Reform in the Midst of Crisis - Reyes, Joel; Kelcey, Jo (World Bank, Washington, DC, 2015)
The education resilience assessment for Mali was conducted within a wider programmatic study and technical assistance framework, Mali: impact of the crisis on social sectors. The broad assessment and action plan supported by this framework crosses the education, health, and social protection sectors. This assessment introduces a resilience lens to identify both the risks brought about or accentuated during the recent political and security crisis in the country, and the community and institutional assets that have helped displaced and host communities cope with it. This focus on risks and assets is fundamental to a resilience approach, and are indeed interrelated. In education resilience, the author's stress how the education system protects and fosters the assets of local school actors, but resilience also suffuses the institutional level, contributing to the policies, programs, and resources that address the protection and educational development needs of students. In this Mali education resilience study, the education communities of interest are those displaced from the north, due to the 2012 political and security crisis, and those in the south hosting them. However, the authors also extrapolate lessons learned for the overall education system of Mali. This study benefitted from the resilience (RES)-360°, a rapid mixed-methods assessment methodology focused on resilience. Together, the qualitative interviews and the perception survey also identified those education services that were considered most relevant to protect host and displaced communities and foster longer-term education reforms. This report has four chapters. Chapter one presents the data collected from participating school actors about the risks they faced as a result of the crisis and the assets they used to cope. Chapter two extrapolates some of the implications of these risks and assets for school-based management structures and programs in Mali. Chapter three presents some initial recommendations for aligning relevant education policies and programs in Mali with a resilience-based approach. Chapter four briefly guides the reader to additional relevant research questions and topics that can further support the education reform process in Mali.